Expressão de zif268 no cérebro do lagarto Tropidurus Hispidus após exploração de um ambiente enriquecido. - Santos, José Ronaldo dos (2010)
In the present work, we investigated behavioral changes associated with the increase in Zif268 protein expression within telencephalic areas of the tropical lizard Tropidurus hispidus that correspond to the mammalian hippocampus (HC). We used 13 male individuals of this species, collected at the Federal Agrotechnical School of Rio Grande do Norte, under SISBIO license number 19561-1. Four animals had their brains removed and were submitted to a Western blot with antibodies for the Zif268 protein. The remaining animals were separated in two different groups: a control group (n=4) and an exploration group (n=5). Animals from the exploration group were exposed to an enriched environment with many sensory cues novel to them. Control group animals stayed in the environment they were already habituated to. After 90 min from the onset of exposure to the new environment, animals from both groups were submitted to intracardiac perfusion with fixative, and the brains were removed, cryoprotected and frozen. After that, brains were sectioned at 20 μm and the sections were subjected to immunohistochemistry for the Zif268 protein. We verified that the Zif268 protein is likely conserved in the brain of T. hispidus, which showed antigenicity for the antibody anti-Zif268 made in mammals. In animals from the exploration group, we detected an increase of the Zif268 protein in the Septum, Striatum, Dorsoventricular Area and in cortical areas corresponding to the HC. This increase was proportional to the amount of environmental exploration, with maximum positive correlation in the hippocampal subareas Medial Cortex (R = 0.94 and p = 0.004) and Dorsomedial Cortex (R = 0.92 and p = 0.006). The data corroborate the notion that the reptilian hippocampus, as well as the mammalian HC, plays an important role in spatial exploration.